Brand management : Principles and Practices - Dutta, Kirti (New Delhi : Oxford University Press, 2012)
Brand Management: Principles and Practices is a comprehensive textbook designed for post graduate management programmes students specializing in marketing. It explores core concepts of branding and illustrates them through numerous examples, exhibits, figures, images, case studies, and videos. Divided into five sections, first section gives an introduction to branding, creating a brand, and understanding how organizational culture helps in successful brand management. Second and third sections discuss brand equity, ways of researching and measuring it, and importance of understanding consumers and markets. Further, fourth section explains branding strategies, e-branding, and marketing communications. Last section explores brand architecture, brands over time, and boundary-less brands. Students will find this book useful for its illustrative coverage of the key concepts. The practical applications would also be very useful to practitioners.
Contents note continued: Price-quality -- Symbols -- Competition -- Personnel -- Channel -- Image -- Customer care and service -- Corporate identity -- Positioning by brand endorsement -- Positioning related to specific category of customers -- Usage occasion and time -- Using corporate social responsibility -- Repositioning -- Repositioning strategies -- Case Study 1 Positioning Gone Wrong -- Case Study 1 Airtel---Reinventing the Brand -- pt. IV MANAGING BRANDS -- 9.Branding and the Marketing Programme -- About the Chapter -- Branding and the Marketing Programme---An Introduction -- Product Strategy -- Introduction -- What is a product? -- Product strategy and branding -- Pricing Strategy -- Introduction -- What is pricing? -- Pricing strategy and branding -- Distribution Strategy -- Introduction -- What is distribution? -- Distribution strategy and branding -- Case Study: Micromax---The Indian War Horse -- 10.E-branding---Building the Brand Online -- About the Chapter --
Each chapter is linked with the CD and contains videos and presentations that explain the key concepts and includes exercises(s) for enhancing decision-making abilities. -- Back cover.
Includes bibliographic references and index.
Keywords: Brand name products; Branding (Marketing); Product management